Cross-linked turner base polymer, obtained turner base gas separation membrane and application of cross-linked turner base gas separation membrane
By in-situ crosslinking during polymerization, the cross-linking of cross-linking of cross-linking of cross-linking of cross-linking in the polymerization process, the high-efficiency gas separation membrane is solved, and the high oxygen flux and low The Treger base gas separation membrane with nitrogen flux is suitable for a variety of industrial applications.
Patent Information
- Application Number
- CN202411246384.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-06
AI Technical Summary
The existing gas separation membranes have low separation selectivity and low separation efficiency in light gases such as hydrogen and carbon dioxide, and rely on covalent crosslinking bonds or ionic crosslinking bonds generated by membrane post-treatment, and lack in-situ crosslinking technology. Excellent gas separation performance is obtained.
The crosslinked Teleg base polymer is prepared by in-situ crosslinking during the polymerization process, forming a Teleg base gas separation membrane with high oxygen flux and low nitrogen flux, using diamine monomers and their derivatives The substance reacts with polyamine monomers and their derivatives in dimethoxymethane and trifluoroacetic acid to form a copolymer or homopolymer, and a membrane is prepared by sol-gel method.
It achieves efficient gas separation performance, especially high O2 transmittance and low N2 transmittance. It is suitable for natural gas/bigas deCO2, hydrogen recovery, air separation and other applications, with excellent mechanical strength and chemical stability.
Smart Images

Figure CN119119465A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas separation membranes, and in particular relates to a cross-linked Teleg base polymer, a Teleg base gas separation membrane obtained and applications thereof. Background Art
[0002] Gas separation technology is an indispensable technology in many industrial processes, such as flue gas treatment, hydrogen purification, natural gas decarbonization, air oxygen enrichment and in-situ nitrogen production. Membrane separation technology has developed rapidly in recent years due to its advantages such as high efficiency, convenience and small footprint.
[0003] Membrane oxygen enrichment / nitrogen production is currently an important application scenario of membrane gas separation, accounting for more than 50% of all gas membrane separations. Its most core component is the membrane material, which is required to have high oxygen flux and high oxygen / nitrogen selectivity as well as certain mechanical strength.
[0004] Base (TB) is a new type of self-microporous polymer with high permeability selectivity (Science, 2013, 339, 303), which is a polymer with development potential. Base introduces polyimide to improve gas separation performance, and CN112275146A uses TB polymer treated with phosphoric acid to solve the technical problems of low separation selectivity and low separation efficiency of existing separation membranes for light gases such as hydrogen and carbon dioxide.
[0005] Because the main chain of the molecule contains twisted aromatic ring structure and base unit, the effective stacking of polymer molecular chain is inhibited, and a relatively large free volume is exhibited, which is conducive to gas permeation. At the same time, cross-linking inhibits pore collapse, making it have good heat resistance, solvent resistance, mechanical strength, chemical stability, solvent resistance and other characteristics, making cross-linked TB one of the candidate materials for oxygen / nitrogen separation gas separation membrane materials. CN108291026A proposes that the side chain functional groups of TB polymers can react with corresponding covalent cross-linked polymers to form covalent cross-links or can activate unsubstituted arylene positions to perform nucleophilic aromatic substitution to form covalent cross-links. Similarly, US9018270 describes an interfacial polymerization technology for preparing a thin film composite membrane including a TB thin layer, but it is also not obtained by in-situ cross-linking to obtain a membrane material. Therefore, how to provide a covalent cross-linking bond or ionic cross-linking bond that is not dependent on the post-treatment of the membrane and can also be prepared to obtain a cross-linked membrane to obtain excellent gas separation performance, which will have significant progress in the art. Summary of the invention
[0006] The present invention provides a cross-linked Teleger base polymer, the obtained Teleger base gas separation membrane and application thereof. The polymer can be cross-linked in situ to form a membrane in one step during the polymerization process, and the obtained membrane has excellent gas separation performance, and its permeability to O2 is very high, while its permeability to N2 is very low. It can be used for natural gas / biogas CO2 removal, hydrogen recovery, and air separation.
[0007] In order to achieve the above-mentioned object, the present invention provides a cross-linked tereug base polymer, which is prepared by reacting at least one diamine monomer and its derivatives, or at least one polyamine monomer and its derivatives, or at least one polyamine monomer and its derivatives and at least one diamine monomer and its derivatives with dimethoxymethane and trifluoroacetic acid, wherein the molar amount of dimethoxymethane is 2-4 times that of the amino functional group, and the molar amount of trifluoroacetic acid is 30-200 times that of the amino monomer.
[0008] Preferably, the homopolymer or copolymer formed by polymerization of at least one diamine monomer and its derivatives and at least one polyamine monomer and its derivatives is as shown in the following formula (1) or formula (2):
[0009]
[0010] Wherein, A represents a polyamine moiety, B represents a diamine moiety, and the molar ratio of A to B is 0.0001:1 to 1:0.
[0011] Preferably, the gel fraction of the homopolymer or copolymer is in the range of 0-100.
[0012] Preferably, the diamine moiety is selected from any one of the following groups:
[0013]
[0014] Preferably, the polyamine moiety is selected from any one of the following groups:
[0015]
[0016] The present invention also provides a Teregu base gas separation membrane, which is prepared by using the cross-linked Teregu base polymer described in any of the above technical solutions.
[0017] As a preference, the method comprises the following steps:
[0018] Dissolve at least one diamine monomer and its derivatives, or at least one polyamine monomer and its derivatives, or a homopolymer or copolymer obtained by polymerizing at least one diamine monomer and its derivatives with at least one polyamine monomer and its derivatives in dimethoxymethane in proportion, cool the system to an ice bath, stir thoroughly, then drop a solvent into the system, remove the ice bath after addition, and react at a low temperature of -20-80°C with stirring for 0.01-48h to obtain a low viscosity mixed solution with a viscosity of 1-100000cp;
[0019] The obtained mixed solution is transferred to a culture dish or a glass plate or scraped by a spatula to prepare a polymer homogeneous film by a sol-gel method;
[0020] After the obtained polymer membrane is swollen, the unreacted acid and salt are neutralized, or after the neutralization, Soxhlet extraction is further performed to remove the residue in the polymer, and then drying is performed to obtain the corresponding cross-linked Tereger base polymer membrane.
[0021] Preferably, the solvent added dropwise is trifluoroacetic acid;
[0022] The swelling solvent used for swelling is at least one selected from water, methanol, ethanol, glycerol, n-hexane, n-pentane, dichloromethane, acetone, and toluene;
[0023] The neutralization is carried out by using at least one selected from aqueous ammonia, sodium bicarbonate, and aqueous potassium carbonate solution;
[0024] The solvent used for Soxhlet extraction is at least one selected from anhydrous methanol, anhydrous ethanol, dichloromethane, chloroform and acetone;
[0025] The drying temperature is 40-200℃ and the drying time is 30min-72h.
[0026] Preferably, when the polymer homogeneous membrane is prepared by the sol-gel method, the mass percentage of the polymer in the casting solution is 5-40wt.%;
[0027] The temperature during film formation is 0-40°C and the volatilization time is 2-72h;
[0028] The film thickness is controlled at 10μm-200μm.
[0029] The present invention also provides an application of the Teleger base gas separation membrane according to any of the above technical solutions in at least one of the following: air oxygen enrichment, in-situ nitrogen production, hydrogen concentration, hydrogen-methane separation, and air separation.
[0030] Preferably, when used, the oxygen permeability is 3.0-2000 Barrer, and the oxygen-nitrogen selectivity is 3.6-8.9;
[0031] The hydrogen permeability is 323-15000 Barrer, and the hydrogen-nitrogen selectivity is 16-181.
[0032] Compared with the prior art, the advantages and positive effects of the present invention are:
[0033] 1. The present invention provides a cross-linked Teleg base polymer prepared based on diamine monomers, polyamine monomers and their derivatives. The polymer can use the polyamine monomers as cross-linking sites to form a membrane in one step in situ during the polymerization process to obtain a Teleg base gas separation membrane, and the degree of cross-linking can reach 100%.
[0034] 2. The Teleger base gas separation membrane provided by the present invention has excellent gas separation performance. Specifically, its permeability to O2 is very high, while its permeability to N2 is very low. Therefore, it can be used for air oxygen enrichment, in-situ nitrogen production, hydrogen concentration, hydrogen-methane separation, and air separation, especially for the separate treatment of N2 and O2 in the air. It has great potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 The cross-linked tereuglenoid base homogeneous membrane prepared in Example 8 of the present invention;
[0036] Figure 2 This is a scanning electron microscope (SEM) image of a cross section of a membrane prepared in Example 9 of the present invention;
[0037] Figure 3 This is an enlarged scanning electron microscope (SEM) image of the cross section of the membrane prepared in Example 9 of the present invention;
[0038] Figure 4 (a) of the Teleg base polymer prepared in Example 6 of the present invention 1 H NMR and (b) 13 C NMR spectra;
[0039] Figure 5 The infrared image of the Teleg base polymer prepared in Examples 6-10 of the present invention;
[0040] Figure 6 is the BET diagram of Examples 6-10 of the present invention;
[0041] Figure 7 This is an infrared image of the Teregu base polymer prepared in Example 21 of the present invention. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Examples 1-5
[0044] The homogeneous membrane (Teleger base gas separation membrane) prepared by cross-linking Tereger base polymer has the following molecular structure:
[0045]
[0046] Preparation and characterization of tegrobase-based gas separation membranes:
[0047] Example 1
[0048] 2,6-Diamino-tris(ene) (0.35mmol) and dimethoxymethane (1.75mmol) were added to a 20.0mL reaction bottle, cooled to an ice bath at 0°C, stirred for 10min, and then trifluoroacetic acid (0.9mL) was added dropwise and the ice bath was removed. The reaction was continued to stir at room temperature for 1h, then poured into a petri dish and placed in a fume hood. Finally, a red dry film was obtained after controlling the solvent evaporation for 72h (the air humidity should be less than 30%). The film was soaked in an aqueous solution of ammonia for 12h and then further dried in a vacuum oven at 40°C for 72h. Yield: 98.0%.
[0049] Example 2
[0050] Add 2,6-diamino-trisolene (0.24mmol), 2,6,13(14)-triamino-trisolene (0.08mmol) and dimethoxymethane (1.95mmol) to a 20.0mL reaction bottle, cool to an ice bath, stir for 10min, and then add trifluoroacetic acid (2.0mL) dropwise. After addition, remove the ice bath and stir the reaction at room temperature for 30min. Then transfer to a flat Petri dish in a fume hood. Finally, a red dry film is obtained after controlling the solvent evaporation for 72h (the air humidity should be less than 30%). The film is soaked in an ammonia solution for 24h and then further dried in a tube furnace at 200℃ for 30min. The film thickness is about 80μm (±20μm), and the yield is 97.8%. Solid NMR is tested using powder samples 13 CP-MAS (101MHz, solid state, ppm): δ145.9,137.65,124.26,112.07,67.77,59.00,54.52.
[0051] Example 3
[0052] 2,6-Diamino-trisolene (0.17mmol), 2,6,13(14)-triamino-trisolene (0.17mmol) and dimethoxymethane (2.23mmol) were added to a 20.0mL reaction bottle, cooled to an ice bath, stirred for 10min, and then trifluoroacetic acid (3.0mL) was added dropwise. After the addition, the ice bath was removed and the reaction was stirred at room temperature for 5-30min. The reaction was stirred for another 30-60min at room temperature and then transferred to a flat Petri dish in a fume hood. Finally, a red dry film was obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film was soaked in an ammonia solution for 24h and then further dried in a vacuum oven at 80°C for 48h. The film thickness was approximately 80μm (±20μm), and the yield was 95.5%. Solid NMR was tested using powder samples 13 CP-MAS (101MHz, solidstate, ppm): δ145.9,136.94,123.94,111.22,68.24,59.62,54.86.
[0053] Example 4
[0054] Add 2,6-diamino-trisolene (0.08mmol), 2,6,13(14)-triamino-trisolene (0.24mmol) and dimethoxymethane (2.31mmol) to a 20.0mL reaction bottle, cool to an ice bath, stir for 10min, and then add trifluoroacetic acid (4.0mL) dropwise. After addition, remove the ice bath and stir the reaction at room temperature for 30min. Then transfer to a flat Petri dish in a fume hood. Finally, a red dry film is obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film is soaked in an ammonia solution for 48h and then further dried in a vacuum oven at 120°C for 10h. The film thickness is about 80μm (±20μm), and the yield is 98.5%. Solid NMR is tested using powder samples 13 CP-MAS (101MHz, solid state, ppm): δ145.96,136.76,123.39,110.96,69.0,59.33,55.04.
[0055] Example 5
[0056] 2,6,13(14)-triamino-tridiscene (0.33mmol) and dimethoxymethane (2.48mmol) were added to a 20.0mL reaction bottle, cooled to 0℃, stirred for 10min, and then trifluoroacetic acid (5.0mL) was added dropwise. The reaction was stirred for 1h in an ice bath. Then it was transferred to a petri dish cooled to 0℃ in a fume hood. Finally, a red dry film was obtained after controlling the solvent evaporation for 72h (the air humidity should be less than 30%). The film was soaked in an ammonia solution for 72h and then further dried in a vacuum oven at 150℃ for 10h. The film thickness was about 200μm (±20μm), and the yield was 93.0%. Solid NMR was tested using powder samples 13 CP-MAS (101MHz, solid state, ppm): δ145.8,137.65,123.1,111.1,67.7,59.25,54.22.
[0057] Table 1 Monomer ratios of Examples 1-5
[0058]
[0059] Examples 6-10
[0060] The Tereger base polymer membranes obtained in Examples 1-5 were respectively extracted with anhydrous MeOH for 8 h, and then dried in a vacuum oven at 120° C. for 4 h to obtain Examples 6-10. The membrane thickness of Example 6-9 was 80 μm (±20 μm), and the membrane thickness of Example 10 was 200 μm (±20 μm).
[0061] Digital photos of the membranes of Example 8 are shown in Figure 1 , the cross-linked film exhibits good film-forming properties.
[0062] In addition, the cross-sectional scanning electron microscopy images of Example 9 show that the film exhibits a smooth and defect-free structure, such as Figure 2-3 .
[0063] The structure of Example 6 was characterized by hydrogen and carbon nuclear magnetic resonance spectra. Figure 4 . 1 HNMR (400MHz, CDCl3, ppm): δ7.18(s,2H),6.96(s,2H),6.84(s,2H),6.76(s,2H),5.05(s,2H),4.43(s,2H),3.90(s,4H). 13 C NMR (100MHz, CDCl3): δ144.6,144.0,140.6,140.2,125.2,124.0,123.3,121.6,120.2,66.7,58.2,53.0.
[0064] The films obtained in Examples 6-10 were subjected to Fourier infrared testing. Figure 5 As shown, all films have a peak at 1628 cm -1 The CN characteristic peak appears at ~2950cm -1 The CH stretching vibration peak of -CH2 appeared at , indicating that the TB polymer was successfully synthesized.
[0065] BET test was performed on Examples 6-10. Figure 6 As shown, it can be concluded that its pore distribution is mainly located in Specific surface area is 503-900m 2 / g -1 , which is consistent with the characteristics of microporous polymers.
[0066] Embodiment 11-12:
[0067] The mean membrane (Teleger base gas separation membrane) prepared by cross-linking Tereger base polymer has the following molecular structure:
[0068]
[0069] Preparation and characterization of tegrobase-based gas separation membranes:
[0070] Embodiment 11
[0071] 4,4'-(Hexafluoroisopropylidene)diphenylamine (6FA, 0.9mmol) and 1,3,5-tri(4-aminophenyl)benzene (TPB, 0.1mmol) and dimethoxymethane (5.2mmol) were added to a 50mL reaction bottle, cooled to an ice bath, stirred for 10min, and trifluoroacetic acid (15.0mL) was added dropwise. After addition, the ice bath was removed and the reaction was stirred at room temperature for 1h. The reactants were poured into a petri dish and placed in a fume hood. Finally, a red dry film was obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film was soaked in an aqueous solution of ammonia for 24h. Anhydrous MeOH was extracted with Soxhlet for 8h, and then the film was dried in a vacuum oven at 120℃ for 4h. Thickness 80μm (±20μm).
[0072] Example 12
[0073] 6FA (0.7mmol) and 1,3,5-tris(4-aminophenyl)benzene (TPB, 0.3mmol) and dimethoxymethane (5.6mmol) were added to a 50mL reaction bottle, cooled to an ice bath, stirred for 10min, and trifluoroacetic acid (15.0mL) was added dropwise. After addition, the ice bath was removed and the reaction was stirred at room temperature for 1h. The reactants were poured into a petri dish and placed in a fume hood. Finally, a red dry film was obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film was soaked in an aqueous solution of ammonia for 24h. Anhydrous MeOH Soxhlet extraction was performed for 8h, and then dried in a vacuum oven at 120°C for 4h. Thickness 80μm (±20μm).
[0074] Table 2 Monomer ratios of Examples 11-12
[0075]
[0076] Examples 13-15
[0077] The mean membrane (Teleger base gas separation membrane) prepared by cross-linking Tereger base polymer has the following molecular structure:
[0078]
[0079] Preparation and characterization of tegrobase-based gas separation membranes:
[0080] Example 13
[0081] 2,6-Diamino-tridiscene (TDA, 0.9mmol) and TPB (0.1mmol) and dimethoxymethane (5.2mmol) were added to a 50mL reaction bottle, cooled to an ice bath, stirred for 10min, and trifluoroacetic acid (15.0mL) was added dropwise. After addition, the ice bath was removed and the reaction was stirred at room temperature for 1h. The reactants were poured into a petri dish and placed in a fume hood. Finally, a red dry film was obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film was soaked in an aqueous solution of ammonia for 24h. Anhydrous MeOH Soxhlet extraction was performed for 8h, and then dried in a vacuum oven at 120°C for 4h. Thickness 80μm (±20μm).
[0082] Embodiment 14
[0083] 2,6-Diamino-tridiscene (TDA, 0.5mmol) and TPB (0.5mmol) and dimethoxymethane (6.0mmol) were added to a 50mL reaction bottle, cooled to an ice bath, stirred for 10min, and trifluoroacetic acid (15.0mL) was added dropwise. After addition, the ice bath was removed and the reaction was stirred at room temperature for 1h. The reactants were poured into a petri dish and placed in a fume hood. Finally, a red dry film was obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film was soaked in an aqueous solution of ammonia for 24h. Anhydrous MeOH Soxhlet extraction was performed for 8h, and then dried in a vacuum oven at 120℃ for 4h. Thickness 80μm (±20μm).
[0084] Embodiment 15
[0085] 2,6-Diamino-tridiscene (TDA, 0.25mmol) and TPB (0.75mmol) and dimethoxymethane (6.5mmol) were added to a 50mL reaction bottle, cooled to an ice bath, stirred for 10min, and then trifluoroacetic acid was added dropwise. After addition, the ice bath was removed and the reaction was stirred at room temperature for 1h. The reactants were poured into a petri dish and placed in a fume hood. Finally, a red dry film was obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film was soaked in an aqueous solution of ammonia for 24h. Anhydrous MeOH Soxhlet extraction was performed for 8h, and then dried in a vacuum oven at 120°C for 4h. Thickness 80μm (±20μm).
[0086] Table 3 Monomer ratios of Examples 13-15
[0087]
[0088] Examples 16-20
[0089] The mean membrane (Teleger base gas separation membrane) prepared by cross-linking Tereger base polymer has the following molecular structure:
[0090]
[0091] Preparation and characterization of tegrobase-based gas separation membranes:
[0092] Example 16
[0093] Add 3,3'-dimethylbenzidine (DMA, 0.35mmol) and dimethoxymethane (1.75mmol) to a 20mL reaction bottle, cool to an ice bath, stir for 10min, and then add trifluoroacetic acid (5.0mL) dropwise. After addition, remove the ice bath and stir the reaction at room temperature for 1h. Pour the reactants into a petri dish and place it in a fume hood. Finally, a red dry film is obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film is soaked in an aqueous solution of ammonia for 24h. Anhydrous MeOH Soxhlet extraction for 8h, then dried in a vacuum oven at 120℃ for 4h. Thickness 40μm (±10μm).
[0094] Embodiment 17
[0095] 3,3'-Dimethylbenzidine (DMA, 0.24mmol), TPB (0.08mmol) and dimethoxymethane (1.95mmol) were added to a 20mL reaction bottle, cooled to an ice bath, stirred for 10min, and trifluoroacetic acid (5.0mL) was added dropwise. After addition, the ice bath was removed and the reaction was stirred at room temperature for 1h. The reactants were poured into a petri dish and placed in a fume hood. Finally, a red dry film was obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film was soaked in an aqueous solution of ammonia for 24h. Anhydrous MeOH Soxhlet extraction was performed for 8h, and then dried in a vacuum oven at 120℃ for 4h. Thickness 140μm (±20μm).
[0096] Embodiment 18
[0097] Add DMA (0.17mmol), TPB (0.17mmol) and dimethoxymethane (2.23mmol) to a 20mL reaction bottle, cool to an ice bath, stir for 10min, and then drop trifluoroacetic acid (5.0mL). After addition, remove the ice bath and stir the reaction at room temperature for 1h. Pour the reactants into a petri dish and place it in a fume hood. Finally, a red dry film is obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film is soaked in an aqueous solution of ammonia for 24h. Extract with anhydrous MeOH for 8h, and then dry in a vacuum oven at 120℃ for 4h. Thickness 140μm (±20μm).
[0098] Embodiment 19
[0099] Add DMA (0.08mmol), TPB (0.24mmol) and dimethoxymethane (2.31mmol) to a 20mL reaction bottle, cool to an ice bath, stir for 10min, and then add trifluoroacetic acid (5.0mL) dropwise. After addition, remove the ice bath and stir the reaction at room temperature for 1h. Pour the reactants into a petri dish and place it in a fume hood. Finally, a red dry film is obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film is soaked in an aqueous solution of ammonia for 24h. Extract with anhydrous MeOH for 8h, and then dry in a vacuum oven at 120℃ for 4h. Thickness 140μm (±20μm).
[0100] Embodiment 20
[0101] Add TPB (0.33mmol) and dimethoxymethane (2.48mmol) to a 20mL reaction bottle, cool to an ice bath, stir for 10min, and then add trifluoroacetic acid (5.0mL) dropwise. After addition, remove the ice bath and stir the reaction at room temperature for 1h. Pour the reactants into a petri dish and place it in a fume hood. Finally, a red dry film is obtained after controlling the solvent evaporation for 48h (the air humidity should be less than 30%). The film is soaked in an aqueous solution of ammonia for 24h. Extract with anhydrous MeOH for 8h, and then dry in a vacuum oven at 120°C for 4h. Thickness 140μm (±20μm).
[0102] Table 4 Monomer ratios of Examples 16-20
[0103]
[0104] Embodiment 21
[0105] The homogeneous membrane (Teleger base gas separation membrane) prepared by cross-linking Tereger base polymer has the following molecular structure:
[0106]
[0107] Embodiment 21
[0108] Take 100 mg of 4',5'-bis(4-aminophenyl)-[1,1':2',1"-terphenyl]-4,4"-diamine (Mn=442, 0.443 mmol) and add it to a 20 mL reaction bottle. After adding 0.2 mL of dimethoxymethane (0.265 g, 3.5 mmol, 8 eq), stir the reaction in an ice-water bath for 30 min, then slowly add 5.0 mL of trifluoroacetic acid, and the solution turns black. After stirring for 30 min, pour the reactants into a culture dish and place it in a fume hood overnight to form a tetraamine cross-linked TB film. The film was soaked in an aqueous solution of ammonia for 24 h. Extract with anhydrous MeOH for 8 h, and then dry in a vacuum oven at 120°C for 4 h. Thickness 80 μm (±20 μm). The film obtained in Example 21 was tested by Fourier infrared. Figure 7 Shown at 1608cm -1 The CN characteristic peak appears at ~2950cm -1 The CH stretching vibration peak of -CH2 appears at , indicating the successful synthesis of Example 21.
[0109] Embodiment 22
[0110] The Tereger base polymer film obtained in Example 9 was Soxhlet extracted with dichloromethane for 8 h and then dried in a vacuum oven at 120° C. for 4 h.
[0111] Embodiment 23
[0112] Example 23 is a film of the Teregu base polymer film obtained in Example 9 after aging for one month under vacuum plastic sealing conditions.
[0113] Determination of pure gas permeability and selectivity:
[0114] The packaged membrane was placed in a constant volume variable pressure method test device. After the instrument was evacuated, 0.2 MPa of the gas to be tested was introduced upstream. The change in the downstream pressure of the test membrane with time was used to obtain the gas permeation per unit time, thereby obtaining its gas flux. The test data are shown in Table 5.
[0115] Table 5 Pure gas separation performance test
[0116]
[0117] Note: The unit of gas permeability of dense membrane is Barrer. The permeation flux and selectivity are measured at 35℃ and pressure of 2bar, 1bar=0.1Mpa.
[0118] The O2 permeability of Example 1 without Soxhlet extraction is 407 Barrer. The O2 / N2 selectivity is 4.7. The permeability of the membrane is also affected by the post-treatment method. For example, methanol Soxhlet extraction helps to remove impurities in the membrane material and enhance the permeability selectivity of the membrane. The O2 permeability of Example 6 after Soxhlet extraction increases from 407 Barrer to 693 Barrer, and the O2 / N2 selectivity increases from 4.7 to 5.7. When TTA-75 is subjected to Soxhlet extraction with dichloromethane, although the O2 permeability drops to 390 Barrer, the O2 / N2 selectivity can reach 8.9, the H2 permeability is 8000 Barrer, and the H2 / CH4 selectivity is 208, which is the highest PIM material reported so far.
[0119] As the triamine content of Examples 6-10 increases from 0 to 100%, their permeability selectivity increases simultaneously. For example, the O2 permeability increases from 693 Barrer in Example 6 to 1654 Barrer in Example 10, and the O2 / N2 selectivity also gradually increases from 5.7 to 6.6. The change trends of H2 / CH4 and CO2 / CH4 are also the same. This anti-tradeoff effect is due to the following aspects: (i) First, the three-dimensional mesh PIM membrane has a larger microporosity and specific surface area ( Figure 6 ), thereby improving the permeability; (ii) secondly, it also has a high ultramicroporosity, which enhances the size screening ability of the resulting membrane.
[0120] Determination of mixed gas flux and selectivity:
[0121] The packaged membrane of Example 23 was placed in a cross-flow constant volume variable pressure method test device. After the instrument was evacuated, 0.2-1.5 MPa compressed air was introduced upstream. The change in the downstream pressure of the membrane with time was tested to obtain the gas permeation rate per unit time, and the components on the permeation side were analyzed by gas chromatography to obtain the permeability of each gas pair. The test results are shown in Table 6.
[0122] Table 6 Mixed gas separation performance test
[0123]
[0124] Note: The unit of gas permeability of dense membrane is Barrer. The permeation flux and selectivity are measured at 35℃ and pressure 2-15bar, 1bar=0.1Mpa.
[0125] Due to the excellent gas separation performance of Example 23, the O2 / N2 mixed gas separation performance of Example 23 was studied. In the mixed gas test, the O2 / N2 permeability decreased due to competitive adsorption. For example, when the pressure increased from 2 bar to 15 bar, the O2 permeability continued to decrease from 740 Barrer to 654 Barrer, but the mixed gas selectivity of O2 / N2 at different pressures was still ~7.2. The overall pressure-dependent performance of O2 / N2 mixed gas separation is still higher than the latest 2015 O2 / N2 pure gas upper limit, and is much better than the most advanced membranes reported, which shows great potential for O2 enrichment and N2 generation industries.
Claims
1. A cross-linked tereug base polymer, characterized in that The invention is prepared by reacting at least one diamine monomer and its derivatives, or at least one polyamine monomer and its derivatives, or at least one polyamine monomer and its derivatives and at least one diamine monomer and its derivatives with dimethoxymethane and trifluoroacetic acid, wherein the molar amount of dimethoxymethane is 2-4 times that of the amino functional group, and the molar amount of trifluoroacetic acid is 30-200 times that of the amino monomer.
2. The cross-linked tereug base polymer according to claim 1, characterized in that The structural formula of the homopolymer or copolymer formed by polymerizing at least one diamine monomer and its derivatives with at least one polyamine monomer and its derivatives is as shown in the following formula (1) or formula (2): Wherein, A represents a polyamine moiety, B represents a diamine moiety, and the molar ratio of A to B is 0.0001:1 to 1:
0.
3. The cross-linked tereug base polymer according to claim 2, characterized in that The gel fraction of the homopolymer or copolymer ranges from 0 to 100.
4. The cross-linked tereug base polymer according to claim 2 or 3, characterized in that The diamine moiety is selected from any one of the following groups:
5. The cross-linked tereug base polymer according to claim 2 or 3, characterized in that The polyamine moiety is selected from any one of the following groups:
6. A Teregu base gas separation membrane, characterized in that: The cross-linked tereug base polymer is prepared by using any one of claims 1 to 5.
7. The Tereger base gas separation membrane according to claim 6, characterized in that: The following steps are involved: Dissolving at least one diamine monomer and its derivatives, or at least one polyamine monomer and its derivatives, or at least one polyamine monomer and its derivatives and at least one diamine monomer and its derivatives in dimethoxymethane, cooling the system to an ice bath, stirring thoroughly, then dropping trifluoroacetic acid into the system, removing the ice bath after the addition, and stirring the reaction at a low temperature of -20-80°C for 0.01-48h to obtain a low viscosity mixed solution with a viscosity of 1-100000cp; The obtained mixed solution is transferred to a culture dish or a glass plate or scraped by a spatula to prepare a polymer homogeneous film by a sol-gel method; After the obtained polymer membrane is swollen, the unreacted acid and salt are neutralized, or after the neutralization, Soxhlet extraction is further performed to remove the residue in the polymer, and then drying is performed to obtain the corresponding cross-linked Tereger base polymer membrane.
8. The Tereger base gas separation membrane according to claim 7, characterized in that: The swelling solvent used for swelling is at least one selected from water, methanol, ethanol, glycerol, n-hexane, n-pentane, dichloromethane, acetone, and toluene; The neutralization is carried out by using at least one selected from aqueous ammonia, sodium bicarbonate, and aqueous potassium carbonate solution; The solvent used for Soxhlet extraction is at least one selected from anhydrous methanol, anhydrous ethanol, dichloromethane, chloroform and acetone; The drying temperature is 40-200℃ and the time is 30min-72h; When the polymer homogeneous membrane is prepared by the sol-gel method, the mass percentage of the polymer in the casting solution is 5-40wt.%; The temperature during film formation is 0-40°C and the volatilization time is 2-72h; The film thickness is controlled at 10μm-200μm.
9. Use of the Teleger base gas separation membrane according to any one of claims 6 to 8 in at least one of air oxygen enrichment, in-situ nitrogen production, hydrogen concentration, hydrogen-methane separation, and air separation.
10. The use according to claim 9, characterized in that: When used, the oxygen permeability is 3.0-2000 Barrer, and the oxygen-nitrogen selectivity is 3.6-8.9; The hydrogen permeability is 323-15000 Barrer, and the hydrogen-nitrogen selectivity is 16-181.
Citation Information
Patent Citations
Phosphoric acid treated Trogers Base polymer gas separation membrane as well as preparation method and application thereof
CN112275146A
Preparation method and application of mixed matrix membrane for realizing efficient gas separation through in-situ crosslinking
CN114870655A
Ionized Troger base high polymer material as well as preparation method and application thereof
CN115636936A
Monovalent and bivalent anion separation membrane based on microporous polymer as well as preparation method and application of monovalent and bivalent anion separation membrane
CN118437164A
Cited By
Charged Janus special base membrane as well as preparation method and application thereof
CN120988328A
